Tasik Biru as a Modern Analogue for the Ancient Ocean -An International Research Collaboration - Samuel, Lihan (IBEC, UNIMAS, 2024)
A research collaboration activity between researcher from IBEC and researchers from Universities in Germany, USA and Mexico was carried out at Tasik Biru on June 10- 16, 2024. The group from the international was led by Dr Muammar Mansor from University of Tuebingen, Germany. The research plan was to: (1) conduct water sampling and multiparameter analysis using Sonde (pH, temperature, DO, etc.) in Tasik Biru, (2) filter microorganisms on filter paper, extract DNA, carry out NGS sequencing & bioinformatic analysis, (3) conduct biominerals analysis with electron microscopy & X-ray diffraction, (4) preserve lake sediment with fixatives (glutaraldehyde) and kept frozen for further analysis.